Angioimmunoblastic T-cell Lymphoma: A Case Report - Sundus Nasim; Dua Azim; Farheen Malik; Faryal Tahir; Zehra Ashraf; Abdul Qayyum (ziauddin University, 2024)
Angioimmunoblastic T-cell lymphoma (AITL) is a rare, aggressive type of non-Hodgkin's lymphoma (NHL) that is mostly diagnosed in elderly patients. Its non-specific clinical presentation (lymphadenopathy, fever, night sweats, weight loss, generalized rash, and hepatosplenomegaly) often results in a delay in the diagnosis. The diagnosis is mainly established based on a detailed clinical evaluation and biopsy findings, and currently, available treatment options include corticosteroids, immunotherapy, and single- or multi-agent chemotherapy. Here, we report a case of a 61-year-old male who presented with complaints of easy fatigability, dyspnea, and fever along with inguinal lymphadenopathy and was diagnosed as a case of AITL. He was given multiple cycles of R-CHOP chemotherapy (Cytoxan, Hydroxyrubicin, Oncovin, Prednisone chemotherapy regimen), which led to tumor eradication. The patient, however, expired due to unknown reasons. The case highlights the major diagnostic modalities and treatment strategies for AITL and sheds light on the poor prognosis of the disease despite adequate management. Keywords: Angioimmunoblastic